ANALISIS PENGARUH SUHU PERMUKAAN LAUT DI SAMUDRA HINDIA PADA KALA HOLOSEN TENGAH TERHADAP MIGRASI INTERTROPICAL CONVERGENCE ZONE (ITCZ) - Maharani, Adinda
The increased insolation in the boreal summer during the mid-Holocene give affected to Asian Continent to have a warmer temperature compared to today. The increased temperature can the impact enhanced Asian precipitation. A lot of the study about proxy and model simulation of the changes of global surface temperature and precipitation have been done. But the specific study about the impact of the sea surface temperature (SST) in the Indian Ocean to Asian rainfall is still not much. Whereas, the dynamic of SST Indian Ocean has influenced to distribution of precipitation in Asian Continent during mid-Holocene. This study uses a multi-model analysis of the nine Global Climate Models (GCMs), which are obtained from the database of the Paleoclimate Modelling Intercomparison Project Phase-3 (PMIP3) using two scenarios which are mid-Holocene and pre-Industrial. The pre-Industrial climate will be compared with the mid-Holocene climate. The pre-Industrial climate condition will be described recent climate. The nine GCMs are BCC-CSM1, CCSM4, CESS FGOAL-S2, CSIRO MK-3-6-0, IPSL-CM5A-LR, MPI ESM-P, MIROC ESM, MRI-CGCM3, and NASA GISS-E2. Physical quantities used in this study are monthly rainfall, surface temperature, evaporation, horizontal winds at 850mb, and moisture flux at 850mb. Then a scatter plot analysis was carried out to see the model distribution from each parameter, and the correlation between models was calculated. Correlation calculations were carried out to see the correlation of all models and correlations without CCSM4 and GISS E2-R. The multi-model analysis between the Asian monsoon winds and the Asia-Indian Ocean temperature gradient has a positive correlation of 0.78 for all models. While the multi-model analysis between the Asian monsoon winds (temperature gradient of Asia-Indian Ocean) and Asian rainfall has a negative correlation of –0.15 (-0.67) for all models and -0.07 (-0.88) for the correlation of seven models without GISS E2-R and CCSM4. Asian temperature changes and the Indian Ocean SST influence the Asian-Indian Ocean temperature gradient. Hence, the two regions affect the correlation between the Asia-Indian Ocean temperature gradient and Asian rainfall. Meanwhile, the multi-model relationship between the Asian Continent temperature (Indian Ocean SST) and Asian precipitation has a positive correlation of 0.30 (0.048) for all models and 0.30 (0.61) without CCSM4 and GISS E2R. So based on the correlation results, the decrease in SST in the Indian Ocean affects the negative correlation between the Asia-Indian Ocean temperature gradient and Asian precipitation. Then the relationship between Indian Ocean evaporation and Asia rainfall has a positive correlation of 0.45 for all models and 0.43 for those without CCSM4 and GISS E2R. Meanwhile, the results of multi-model analysis between Indian Ocean SST and Indian Ocean evaporation in increased areas had a positive correlation of 0.06 for all models and 0.43 for without the CCSM4 and GISS E2R models. The multi-model correlation between moisture flux in the Indian Ocean and Asian rainfall (Indian Ocean SST) shows a value of -0.40 (-0.17) for all models and 0.79 (0.57) without CCSM4 and BCC-CSM1 models. The model that simulates the smallest decrease in Indian Ocean SST produces the largest increase in evaporation and moisture flux in the Indian Ocean. Thus, the indications model makes the largest increase in water vapor sources for rainfall in Asia. Hence, the results in a model with the largest increase in rain in Asia.